At skrive gennem lyd: Om Audible Originals - Pedersen, Birgitte Stougaard (Passage - Tidsskrift for litteratur og kritik, 2020)
The article discusses audio first stories as a phenomenon developed from the classic audiobook format. It focuses on so-called Audible Originals, published by the audiobook publisher Audible since 2018. The article is partly based on an interview with the Australian writer Ceridwen Dovey on her Audible Original novel Life after Truth (2019). It deals with original audio stories from four different perspectives: Writing through sound, publishing through sound, genres of sound and of cultural values and hierarchies connected to writing and publishing audio stories.